PERANGKAT PEMBELAJARAN BIOLOGI BERNUANSA KARAKTER MELALUI INQUIRY DALAM PEMBELAJARAN DARING - Sainab Sainab; Herna Herna (Universitas Islam Negeri Sumatera Utara, 2022)
Preliminary studies of needs analysis on the development of biology learning tools show the low learning outcomes of students' cognitive and behavioral characteristics. Therefore, it is necessary to develop learning instruments that aim to develop character-based biology learning tools through inquiry during online learning that achieve valid, useful, and efficient benchmarks. The device consists of four components, namely: lesson plans (RPP), student books (BPD), student worksheets (LKPD), and assessment instruments. This type of research is developmental research by using the 4-D model (four D), which has 4 stages, namely the defining stage, the design stage, the develop stage, and the last stage of dissemination. The final score of the analysis of the validity of the learning instrument states that the biology learning tool with character nuances through inquiry for the sake of improving cognitive and character learning achievement in the online learning period for the subject of plant and animal body structure and function in class XI high school that was developed is suitable to be applied based on the final validation score from validator. Biology learning instruments with character nuances through inquiry so that cognitive and character learning outcomes during the online learning period that are developed are practical and effectively implemented in class XI of high school on the material structure and function of the body of plants and animals have increased. Therefore, biology learning tools with character nuances through inquiry are appropriate to be applied because they have met the practical, valid and effective criteria.